1995
DOI: 10.1002/jor.1100130413
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties of the supraspinatus tendon

Abstract: The tensile properties of the supraspinatus tendon were investigated in 11 shoulders from fresh cadavers. The tendon was divided into three longitudinal strips: anterior, middle, and posterior. Each specimen was mounted on a materials testing machine, with four fluorescent markers placed on both surfaces of the tendon strip. The positions of these markers were recorded during the test by two synchronized video cameras. Load-deformation and strain curves were determined, and the stress-strain curve, strength, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
97
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(109 citation statements)
references
References 24 publications
8
97
2
2
Order By: Relevance
“…Scaffold mechanical properties are directly related to fiber alignment and while they decreased as the polymer degraded, both the elastic modulus (Fig. 4) and ultimate tensile strength remain within range of those reported for the native supraspinatus tendon 128 .…”
Section: Stratified Scaffold For Tendon-bone Interface Tissue Engsupporting
confidence: 69%
“…Scaffold mechanical properties are directly related to fiber alignment and while they decreased as the polymer degraded, both the elastic modulus (Fig. 4) and ultimate tensile strength remain within range of those reported for the native supraspinatus tendon 128 .…”
Section: Stratified Scaffold For Tendon-bone Interface Tissue Engsupporting
confidence: 69%
“…The importance of the supraspinatus tendon and rotator cable in maintaining normal glenohumeral abduction torque has been suggested biomechanically 5,19 . Additionally, the anterior aspect of the supraspinatus tendon has been shown to have the highest tensile strength compared to the middle and posterior regions of the tendon 7 . Mesiha et al demonstrated the importance of the anterior supraspinatus insertion noting increased gapping, stiffness and regional tendon strains in experimental tears of the anterior supraspinatus tendon compared to tears isolated to the rotator crescent 16 .…”
Section: Discussionmentioning
confidence: 99%
“…This prevention of tendon injury may be related to decrease in the elastic modulus of the tendon. On the other hand, a tear of the supraspinatus tendon typically starts at the anterior one-third of the tendon (Tuite et al 1998, Matsen et al 2004), where the elastic modulus is greater than in the middle third or the posterior third (Itoi et al 1995). Based on these findings, it is likely that the greater the modulus of elasticity, the greater the risk of tendon rupture.…”
Section: Discussionmentioning
confidence: 99%